Alternative anode geometry for magnetron sputtering - Petroski, Kleber Alexandre [UNESP]; Sagás, Julio César (Elsevier, 2020)
Anode geometry can play a crucial role in magnetron sputtering deposition. In this work, we investigated the use of five different ring anodes placed in front of the target. Their effects in the current-voltage relations and the hysteresis curves in reactive deposition were compared to conventional magnetron sputtering and grid-assisted magnetron sputtering. We measured the current-voltage relations in Ar discharges using Al and Ti targets. The hysteresis curves were obtained in Ar/N2 and Ar/O2 atmospheres for both targets. By changing the ring internal diameter, we change the ratio between the ring internal diameter and the target diameter. The results show that this ratio is determinant to the current-voltage relations and substrate floating potential, which can vary from negative to positive values relative to the ground. We also report hysteresis in the substrate floating potential during reactive deposition. The analysis of these hysteresis curves shows that the substrate floating potential can decrease to values around – 60 V depending on target/reactive gas combination.
Keywords: Current-voltage relations; Hysteresis curves; Magnetron sputtering; Substrate floating potential